Nurse Jackie. Season one [videorecording (DVD)] - Dunsky, Evan, 1957-; Brixius, Liz; Wallem, Linda, 1961- (Lionsgate, 2010)
Jackie Peyton is a sharp-tongued and quick-witted nurse who is trying to survive the chaotic grind of saving lives in a hectic New York City hospital. Jackie's a woman of substance who knows how to handle it all. With a white lie here, a bent rule there, and a steady dose of pain relievers for her chronic back pain, Jackie does whatever it takes to get the job done.